Zur aktuellen Krisenstimmung im Wohnungsbau - Felix Leiss; Klaus Wohlrabe (Wirtschaftsdienst, 2024)
– This article examines the recent downturn in Germany's housing construction sector, marked by a significant drop in business climate indicators. Key factors include material shortages, order cancellations, financing constraints, and a lack of new orders, which have worsened since the COVID-19 pandemic and the Ukraine war. A central driver for this development was the sharp and rapid increase of the ECB's key interest rate and the subsequently deteriorating financial conditions for house building. A comparison with other European countries is also provided. The outlook remains bleak, with continued pessimism expected in the housing construction sector.
Keywords: R30; R31; 330; Wohnungsbau; Branchenentwicklung; Deutschland; Wohnungsbau; Branchenentwicklung; Deutschland